STUDI KOMPARASI KEPERCAYAAN DIRI BERDASARKAN TIPE KEPRIBADIAN SISWA SMP - Badiah, Lailatul; Purwanti, Purwanti; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the comparison of self-confidence based on the personality type of Grade VII students of SMP Sungai Raya 2. The problem in this study is "how is self-confidence in terms of the personality type of class VIII students of SMP Negeri 03 Sungai Raya". The purpose of this study was to obtain information and clarity and describe self-confidence in terms of the personality type of class VIII students of SMP Negeri 03 Sungai Raya. The method used is descriptive with a quantitative approach in the form of comparative research. Samples taken were 61 students. The data collection technique used is indirect communication in the form of a questionnaire. Data analysis techniques are percentage and one way ANOVA test. Overall, the confidence of eighth grade students in SMP Negeri 3 Sungai Raya based on sanguinis personality types gained 81% high or good categories, melancholy personality types 76% high or good, choleric personality types 80% high or good categories and phlegmatic personality types 66 % medium category or good enough. And it does not show a significant difference in self-confidence based on the personality type of class VIII students in SMP Negeri 3 Sungai RayaÂ Keywords: Self Confidence, Personality Type